A legal study of the effectiveness of Poisons Act 1952 in regulating possessions of 'Ketum' offence / Mohd Hafizi Hanapi - Hanapi, Mohd Hafizi (2018)
Possession of 'Ketum' is no strangers and this offence is increasing year by year. Criminals prefer to use 'Ketum' from dangerous drugs because 'Ketum' is easy to find and the price is cheaper than other dangerous drugs. Furthermore, the sentences of possession of 'Ketum' is lower than sentences to other dangerous drugs because 'Ketum' is considered as poison and listed under Poisons Act 1952; not under Dangerous Drugs Act 1952. Heroin is one of the example under dangerous drugs which have same effect with 'Ketum' but it is listed under Dangerous Drugs Act 1952. Hence, the offender will may repeat committing the crime because the sentence is lower and inadequate to give lessons to the offender. This research to analyses about the adequacy of Poisons Act 1952 in regulating possession of 'Ketum' and other relevant statutes that can be used to regulate possession of 'Ketum' comparing with other countries such as Thailand. End of this chapter, the author will show that, Poisons Act 1952 is inadequate in regulating possession of 'Ketum' offences.